EFFECTIVE METHODS OF INTRODUCING NEW TECHNOLOGIES INTO THE TEACHING OF FOOTBALL SPORTS: EFFECTIVE METHODS OF INTRODUCING NEW TECHNOLOGIES INTO THE TEACHING OF FOOTBALL SPORTS - soliyev, farux (Физическое воспитание, спорт и здоровье, 2022)
Effective ways of introducing new technologies in football teaching in order to increase the intensity of training are discussed.